Implementasi Teknologi Ramah Lingkungan untuk Menunjang Sektor Pertanian di Desa Margohayu Karangawen Demak - M. Al Haris; Dannu Purwanto; Ali Imron; RA. Qonita Syalsabilla Handayani; Arya Praditya (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Margohayu village is one of the regions in the Karangawen Subdistrict, Demak Regency, Central Java. Desa Margohayu has a population of 8,056, with the majority working as farmers. Currently, the irrigation of rice fields in Desa Margohayu still relies on fossil fuel-based energy, which gradually depletes and has environmental consequences. However, Desa Margohayu has significant potential to establish a self-sustaining energy system by harnessing solar energy. Sunlight can be converted into electricity through solar panels to power water pumps. Therefore, the Community Service Team from Universitas Muhammadiyah Semarang proposes an environmentally friendly and sustainable technology implementation in the agricultural sector through the Margo Mulyo Farmer Group in Desa Margohayu. The goal is to reduce the negative impact of fossil fuel usage that has been prevalent. The results of this initiative show that the Margo Mulyo Farmer Group gains knowledge and skills related to solar energy utilization. The implementation of this technology is expected to reduce agricultural costs, particularly in the irrigation process.